Percepatan Proyek Pembangunan Jalan Tol Akses Makassar New Port dengan Metode Critical Path Method (CPM) Pada PT Jalan Tol Seksi Empat - Nurhayati Rauf; Ahmad Padhil; Andi Fikram Fakriyanzah; Anisa Nurjannah (Department of Industrial Engineering, Universitas Jenderal Soedirman., 2024)
PT Wijaya Karya Beton Tbk is a construction company tasked with carrying out the Makassar New Port (MNP) Toll Access Road Construction Project. The project realization schedule was delayed, which had a negative impact on the Company. Solving this problem can be done using the CPM (Critical Path Method) method. This method is a method for planning and supervising system projects that use network formation principles. The results of the calculation analysis were carried out manually and using the help of POM and QM software. The results obtained from processing data on the duration of work on the construction of the Makassar New Port Access Toll Road used the CPM method, where with this method the results of work were obtained for 36 calendar weeks with a time acceleration of 2 weeks from the results of work carried out by the company. And by using CPM you can find out in more detail the critical activities and non-critical activities which, if used effectively, will provide sufficient opportunity to schedule project activities.